DESIGN OF TS GRADE GUIDING ANTI-COLLISION PAD BASED ON TOPOLOGY OPTIMIZATION (MT) - SUN YuHao; LEI ZhengBao (Jixie qiangdu)
In order to solve the problem of single design method of the existing guided anti-collision pad, the guided anti-collision pad is designed to meet the requirements of the current regulations, and based on the collision-resistant topology optimization method, by establishing the model of the car-anti-collision pad and topologically carrying out the topology optimization analysis under the condition of its positive encounter, from which to extract the basic configuration of the energy absorption unit, to the positive collision of the car center acceleration size as an evaluation index, the use of orthogonal design and robust design method to further optimize the size of the energy absorption unit, and finally obtain the optimal size of the energy absorption unit. The simulation results show that the design method based on collision resistance topology optimization is effective, and the TS-grade guided anti-collision pad is designed to meet the current requirements